The world's most popular manga dragon ball : the monkey king - Toriyama, Akira (San Francisco : VIZ Media, 2021)
Goku's quiet life is disrupted when he meets Bulma, who is searching for seven Dragon Balls. If she collects all seven, the Eternal Dragon will grant her wish. Since the balls are scattered all over the planet, she needs Goku's help
VOL 1